Isolation of a Cyclopentasilane from Magnesium Reduction of a Linear Hexasilane. Issue 33 (1st September 2021) - Ballestero‐Martínez, Ernesto; Ferguson, John T.; Siegler, Maxime A.; Klausen, Rebekka S.
Abstract: The reductive cyclization of two linear hexasilanes is contrasted, where a methylated precursor yielded a cyclohexasilane while the tert ‐butyl‐functionalized analog unexpectedly yielded a cyclopentasilane. A comprehensive analysis using X‐ray diffraction, IR, HR, HRMS, and multinuclear ( 1 H, 13 C and 29 Si) 1D and 2D NMR spectroscopy identified the 1, 2‐dihydrodisilane t BuPhHSi‐SiHPh t Bu as an additional product, which was interpreted as supportive of a mechanism involving silylene elimination. The results of this study may prove informative about substituent effects in the practice of complex organosilicon molecular synthesis. Abstract : The Mg 0 promoted reduction of a sterically hindered 1, 6‐dibromohexasilane yielded a cyclopentasilane as the main product. The disilane t ‐BuPhHSi‐SiHPh t ‐Bu was identified as a minor product, which suggests a possible mechanism involving elimination of a transient silylene SiPh t‐ Bu.